Membangun Strategi Promosi Melalui Media Sosial Tiktok pada UMKM Smoothies Pasmaling - Leni Sugiyanti; Rendy Permana; Melyona Zenia Rabbil; Anna Fajarwaty; Ellynawati Ellynawati; David Chandrawan; Tegar Dwi Hendrawan (Journal of Community Service and Engagement, 2026)
This study examines the implementation of a TikTok-based promotional strategy for a small and medium enterprise (SME), Smoothies PasMaling, within the context of community engagement activities. Employing a qualitative participatory approach, the program involved intensive mentoring, direct observation, and iterative content development to enhance digital marketing capabilities. The findings reveal that structured visual content emphasizing product authenticity effectively attracts audience attention, while the integration of operational information such as location and schedule improves accessibility and consumer interaction. The study further identifies a significant increase in audience engagement, including active communication and user-generated responses, which contributes to the formation of positive electronic word of mouth. These dynamics translate into measurable business outcomes, including increased sales volume, broader market reach, and improved customer loyalty. In addition, the intervention strengthens the partner’s capacity to independently manage digital marketing strategies. The study highlights the importance of aligning creative content, interactive communication, and data-driven adaptation in developing sustainable digital promotion strategies for SMEs in the platform-based economy.